Reframing the L2 learning experience as narrative reconstructions of classroom learning - Hiver, Phil; Obando, Gabriel; Sang, Yuan; Tahmouresi, Somayeh; Zhou, Ashlee; Zhou, Yang (Studies in Second Language Learning and Teaching, 2019)
In this study we investigate the situated and dynamic nature of the L2 learning experience through a newly-purposed instrument called the Language Learning Story Interview, adapted from McAdams’ life story interview (2007). Using critical case sampling, data were collected from an equal number of learners of various L2s (e.g., Arabic, English, Mandarin, Spanish) and analyzed using qualitative comparative analysis (Rihoux & Ragin, 2009). Through our data analysis, we demonstrate how language learners construct overarching narratives of the L2 learning experience and what the characteristic features and components that make up these narratives are. Our results provide evidence for prototypical nuclear scenes (McAdams et al., 2004) as well as core specifications and parameters of learners’ narrative accounts of the L2 learning experience. We discuss how these shape motivation and language learning behavior.